Glaucoma Diagnosis Based on Retinal Fundus Image: A Review - Mahdi, Hussein; El Abbadi , Nidhal (Iraqi Journal of Science, 2022)
Glaucoma is one of the most dangerous eye diseases. It occurs as a result of an imbalance in the drainage and flow of the retinal fluid. Consequently, intraocular pressure is generated, which is a significant risk factor for glaucoma. Intraocular pressure causes progressive damage to the optic nerve head, thus leading to vision loss in the advanced stages. Glaucoma does not give any signs of disease in the early stages, so it is called "the Silent Thief of Sight". Therefore, early diagnosis and treatment of retinal eye disease is extremely important to prevent vision loss. Many articles aim to analyze fundus retinal images and diagnose glaucoma. This review can be used as a guideline to help diagnose glaucoma. It presents 63 articles related to the applications of fundus retinal analysis. Applications of the glaucomatous image classification are improving fundus images by locating and segmenting the optic disc, optic cup, fovea, and blood vessels. The study also presents datasets, metrics, and parameters that indicate the changes in retina structure and the steps and results for each paper.